The Health-Related Quality of Life of Patients Waiting for Anterior Cruciate Ligament Reconstruction Is Worse Than an Age- and Sex-Matched Population: Increasing Time on Waiting List for Surgery Was Independently Associated with a Worse Quality of Life - Siddharth Sripada; Harrison Loader; Man Hei Marcus Kam; Arslan Khaliq Raja; Joshua Haggart; Thomas Fawcett; Cameron Peattie; Samuel Molyneux; Nicholas Clement (Advances in Orthopedics)
Background. The aims of this study were to assess the health-related quality of life (HRQoL) of patients awaiting anterior cruciate ligament (ACL) reconstruction compared to the population at risk: whether knee-specific function was predictive of HRQoL and to identify factors associated with a worse HRQoL. Methods. Sixty-seven patients (male, n = 50; female, n = 17; mean age, 29) identified from the surgical waiting list completed a questionnaire that included demographics, BMI, time of injury, EuroQol 5-dimension (EQ-5D), Short-Form (SF-36), and International Knee Documentation Committee (IKDC) scores. Age- and sex-matched HRQoL data were obtained from population level data. Results. The mean EQ-5D score for the study cohort was significantly worse than the matched score (difference, 0.367; p<0.001), and the same trend was observed for all eight dimensions of the SF-36 score. Thirty-three (49%) patients felt their health, in general, was somewhat or much worse compared to one year ago. There was a correlation between IKDC and EQ-5D scores (r = 0.540, p<0.001). Linear regression was used to formulate the EQ-5D score: EQ-5D = (IKDCx0.013)–0.015 (constant). The SF-36 physical component and length of time on the waiting list were independently associated with the HRQoL, with each 14-point drop or for every 200 days, a clinically significant deterioration in patients’ HRQoL occurred, respectively. Conclusions. Patients had a significantly worse HRQoL when compared to the age- and sex-matched population, which deteriorates with worsening physical function and increasing length of time on the waiting list. The knee-specific IKDC correlated with HRQoL and could be used to estimate the EQ-5D score.